Evaluasi Program Pengendalian Penyakit Demam Berdarah Dengue (DBD) di Kota Semarang Tahun 2011 (Studi di Dinas Kesehatan Kota Semarang) - Kusumo, Rika Adi; Setiani, Onny; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2014)
Background: Based on the number of morbidity (Incidence Rate/IR) from 2008 to 2011, DHF in Semarang was ranked first in Central Java .DHF control program in Semarang consists of six aspects, they are the Human Resources (HR), finance, methods, regulations, infrastructure, and community participation. The purpose of this study was to analyze and evaluate the DHF control program in Semarang which include six aspects. Methods:This research used qualitative research. Triangulation was done by conducting interviews on DHF control management with DHF program managers at Department of Health in Semarang, DHF program managers at puskesmas, and community. DHF control program includes inputs, processes and outputs and outcomes. Results: HR quantity of inputs was less 65% for entomologist or epidemiologist, in terms of quality (qualification), HR was sufficient by education level and still less to 50 % based training followed. Financial aspect has been fulfilled properly, according to the proposed budget, but there are still remaining on the implementation of the budget. Outputs from method consists of reporting covers 90%; PE results < 24 hours at 79%; fogging < 5 days at 64%; PJR once a week at 13%; PJB at 100%. Facilities and infrastructure consists of fogging machines, Personal Protect Equipment, ambulances, loudspeaker, and flashlight was sufficient 100%. Laboratorium examination was not accurate. Regulation was implemented by 90%. The results ofÂ  PSN illustrated community participation by 84% . While the outcomes of DHF control program for as many as 1,303 cases of DHF cases; IR DHF was 73.87 per 100,000 population; CFR 0.77 % and larvae free number 91.18 %. Conclusion:The conclusion is DHF control program in Semarang is not optimal based on indicator inputs, processes, outputs and outcomes. Key word : DHF control program, evaluation, IR, larvae free number